Perinatal health outcomes and care among asylum seekers and refugees: a systematic review of systematic reviews - Nicola Heslehurst (BMC Medicine, 2018)
Abstract Background Global migration is at an all-time high with implications for perinatal health. Migrant women, especially asylum seekers and refugees, represent a particularly vulnerable group. Understanding the impact on the perinatal health of women and offspring is an important prerequisite to improving care and outcomes. The aim of this systematic review was to summarise the current evidence base on perinatal health outcomes and care among women with asylum seeker or refugee status. Methods Twelve electronic database, reference list and citation searches (1 January 2007–July 2017) were carried out between June and July 2017. Quantitative and qualitative systematic reviews, published in the English language, were included if they reported perinatal health outcomes or care and clearly stated that they included asylum seekers or refugees. Screening for eligibility, data extraction, quality appraisal and evidence synthesis were carried out in duplicate. The results were summarised narratively. Results Among 3415 records screened, 29 systematic reviews met the inclusion criteria. Only one exclusively focussed on asylum seekers; the remaining reviews grouped asylum seekers and refugees with wider migrant populations. Perinatal outcomes were predominantly worse among migrant women, particularly mental health, maternal mortality, preterm birth and congenital anomalies. Access and use of care was obstructed by structural, organisational, social, personal and cultural barriers. Migrant women’s experiences of care included negative communication, discrimination, poor relationships with health professionals, cultural clashes and negative experiences of clinical intervention. Additional data for asylum seekers and refugees demonstrated complex obstetric issues, sexual assault, offspring mortality, unwanted pregnancy, poverty, social isolation and experiences of racism, prejudice and stereotyping within perinatal healthcare. Conclusions This review identified adverse pregnancy outcomes among asylum seeker and refugee women, representing a double burden of inequality for one of the most globally vulnerable groups of women. Improvements in the provision of perinatal healthcare could reduce inequalities in adverse outcomes and improve women’s experiences of care. Strategies to overcome barriers to accessing care require immediate attention. The systematic review evidence base is limited by combining heterogeneous migrant, asylum seeker and refugee populations, inconsistent use of definitions and limited data on some perinatal outcomes and risk factors. Future research needs to overcome these limitations to improve data quality and address inequalities. Systematic registration Systematic review registration number: PROSPERO CRD42017073315.